The transition to national armies in the former Soviet republics, 1988-2005 - Lehrke, Jesse Paul (Routledge contemporary Russia and Eastern Europe series., 2012)
This book looks at the militaries of the late-Soviet and post-Soviet republics. Beginning with the end of the Soviet era, it recognises that the successor states did not spring from nowhere, but inherited a legacy that influenced all that followed. The book discusses how politicians control the instruments that are the manifestation of the state's monopoly on violence, and how society views and supports the military. By taking a bottom up empirical approach that examines the personnel, leaders, organisations and institutions, and their outlook and attitudes, the book presents a comprehensiv.